The effects of partial amniotic carbon dioxide insufflation in an ovine model. (6th November 2018) - Skinner, Sasha; Crossley, Kelly; Amberg, Ben; Kashyap, Aidan; Hooper, Stuart; Deprest, Jan A.; Hodges, Ryan; DeKoninck, Philip
Abstract : What's already known about this topic? PACI enables fetoscopic myelomeningocele repair as a minimally invasive alternative to open fetal surgery. PACI causes fetal hypercapnia and acidosis in sheep. Initial clinical series of fetoscopic myelomeningocele repair using PACI was associated with high rates of PPROM and preterm birth. What does this study add? Increasing PACI pressures results in larger disturbances in fetal acid‐base and uterine blood flow. Unheated, nonhumidified PACI exposure leads to fetal membrane inflammation. Important differences in sheep and human uterine and placental structure must be considered in our study interpretation. Abstract: Objective: We aim to assess the effect of partial amniotic carbon dioxide insufflation (PACI) at increasing pressures on fetal acid‐base, fetal‐placental perfusion, and fetal membrane morphology in an ovine model. Method: Pregnant ewes and fetuses were instrumented under isoflurane anesthesia at 105 days gestation (term 145 days) to monitor utero‐placental blood flow, fetal and maternal blood pressure, heart rate, and blood gas status. One group (n = 6) was exposed to PACI (unheated dry CO2 ), involving 10 mm Hg stepwise increases in insufflation pressure (5 to 25 mm Hg), for 80 minutes followed by 20 minutes of desufflation. Un‐insufflated controls (n = 5) were monitored for 100 minutes. At postmortem, fetal membranes were collected for histological analysis. Results: PACI at 25 mm Hg caused severe fetal hypercapnia (PaCO2 = 143 ± 5 vs 54 ± 5 mm Hg, P < 0.001), acidosis (pH = 6.85 ± 0.02 vs 7.25 ± 0.02, P < 0.001), hypoxia (SaO2 = 31 ± 4% vs 57 ± 4%, P = 0.01), and reduced uterine artery flow (50 ± 15 vs 196 ± 13 mL/min/kg, P = 0.005) compared with controls. These effects were greater at higher PACI pressures. PACI resulted in leukocyte infiltration in the amnion (1.77 × 10 −5 ± 0.61 × 10 −5 vs 0.38 × 10 −5 ± 0.19 × 10 −5 cells/μm 2, P = 0.04) and chorionic membranes (2.94 × 10 −5 ± 0.67 × 10 −5 vs 0.84 × 10 −5 ± 0.42 × 10 −5 cells/μm 2, P = 0.01). Conclusion: Higher PACI pressures results in larger disturbances in fetal acid‐base, uterine blood flow, and fetal membrane inflammation in sheep. Differences between human and sheep utero‐placental structure should be considered.